Artificial cell vesicle-mediated delivery of Catharanthus roseus (L.) G. Don-derived vinca alkaloids for enhanced antitumor efficacy - Zhuang, Xiaodong; Huang, Liangjiu; Liu, Risheng; Guan, Liwen; Fang, Xingyue; Ma, Ting (Frontiers in Bioengineering and Biotechnology, 2025)
Vinca alkaloids, a class of naturally derived antimitotic agents isolated from Catharanthus roseus, have long been established as potent chemotherapeutic drugs for the treatment of various malignancies. Despite their clinical efficacy, the therapeutic utility of vinca alkaloids, such as vincristine, vinblastine, and vinorelbine, is frequently constrained by systemic toxicity, poor bioavailability, and the emergence of multidrug resistance. In this study, we developed a universal strategy to construct cell membrane-derived vesicles for the encapsulation of vinca alkaloids, thereby enhancing their antitumor efficacy. These artificial cell vesicles were fabricated through the extraction and reconstitution of membranes from K562 cells. Following optimization of drug-loading efficiency, the resulting therapeutic vesicles, designated membrane-encapsulated vinca alkaloids (M@VAs), were thoroughly characterized to evaluate their drug delivery performance. An optimally formulated vincristine-loaded vesicle (M@vincristine) was subsequently used to assess its antitumor efficacy both in vitro and in vivo. M@vincristine induced a dose-dependent reduction in cell viability and demonstrated significantly greater tumor suppression than free vincristine. At the administered dose, M@vincristine not only promoted enhanced apoptosis but also modulated the expression of key apoptotic factors and effectively induced cell cycle arrest in the M phase. Following intravenous administration, M@vincristine demonstrated efficient tumor accumulation and superior anti-tumor efficacy compared to free vincristine. This artificial therapeutic platform not only addresses the major limitations associated with the clinical use of vinca alkaloids but also paves the way for the development of novel therapeutic agents with broad clinical applicability.